Interphase structure of carbon fiber reinforced polyamide 6 revealed by microbeam X-ray diffraction with synchrotron radiation. (20th April 2016) - Kobayashi, Daigo; Hsieh, Ya-Ting; Takahara, Atsushi
Abstract: Carbon fiber reinforced polyamide 6 (PA6) films were fabricated in this study. A 2 microns polyamide 6 (PA6) transcrystalline layer with positive type birefringence was observed at the interphase region of PA6 and high modulus carbon fiber (HMCF) by using polarized optical microscopy, while no crystal layer was observed at that of PA6 and standard modulus carbon fiber (SMCF). HMCF exhibited higher nucleation efficacy in PA6 matrix than SMCF during cooling process, investigated by differential scanning calorimetry. The crystal form and orientation at the interphase region was further confirmed by microbeam wide angle X-ray diffraction (μWAXD). The μWAXD results show that α phase is the major crystalline fraction in PA6/HMCF and PA6/SMCF composites and the α crystalline percentage is slightly increase at the transcrystalline layer of PA6/HMCF composite. The μWAXD results also suggest that the a axis of α crystals in the transcrystalline layer are predominantly perpendicular to the fiber direction. Graphical abstract: Highlights: Positive birefringence transcrystalline layer was observed at polyamide 6 (PA6)/high modulus carbon fiber (HMCF) interphase. Transcrystalline layer was not observed at PA6/standard modulus carbon fiber (SMCF) interphase. The crystal form and orientation at the interphase region was confirmed by microbeam wide angle X-ray diffraction (mWAXD).